Tinjauan Ilmiah dan Islam terhadap Perawatan Gigi: Studi Komparatif Hadis dan Medis - Avicenna, Dhio Faris; Setyawan, Ardi Dwi; Kamiila, Aida Salis; Amiruddin, Muhammad; Liizzah, Alya (Maliki Interdisciplinary Journal, 2025)
Dental health is an important aspect of maintaining overall bodily health. Islam, through the teachings of Prophet Muhammad saw., emphasizes the importance of dental hygiene, one of which is by recommending the use of siwak as a natural method for cleaning teeth. The use of siwak not only offers spiritual benefits but also supports physical health. Meanwhile, in modern medicine, dental health is maintained through the use of dental floss, fluoride toothpaste, and regular dental check-ups. These efforts aim to prevent problems such as plaque, caries, and periodontal diseases that affect general health. This study aims to analyze the concept of dental health in Islam based on Hadith and compare it with modern medical approaches. Through literature studies from Islamic and scientific sources, it is found that Islamic teachings, particularly the recommendation to use siwak, align with scientific principles of dental care. Islam not only teaches cleanliness as part of worship but also provides guidelines that are relevant to modern health principles. The integration of Islamic teachings with modern medical practices can increase public awareness of the importance of dental health, thereby helping to prevent various oral-related diseases.